Inovasi Pengolahan Minyak Daun Cengkeh dan Dampaknya terhadap Ketahanan Sosial-Ekonomi Rumah Tangga Petani di Kepulauan Anambas - Abu Hanifah; Mulana Nadzif Fanani Putra Hanfi (Jurnal Riset Multidisiplin Edukasi, 2025)
Clove is one of the leading commodities of the Anambas Islands Regency, yet the utilization of clove leaves has not been optimized and is often considered agricultural waste. Innovation in processing clove leaves into essential oil offers an opportunity to increase added value for farming households. This study aims to analyze the innovation process of clove leaf oil production and assess its impact on the socio-economic resilience of farming households. A mixed-method approach was employed through a quantitative survey of 45 clove farmers, in-depth interviews, and observations of the essential oil processing stages. The results show that the innovation of processing clove leaves can increase farmers’ income by 15–32% per harvest, reduce agricultural waste volume by up to 40%, and strengthen social resilience through enhanced social capital, farmer group collaboration, and livelihood diversification. This innovation also has the potential to support a circular economy and create opportunities for household-scale agro-industry in island areas. The study concludes that processing clove leaf oil is an effective strategy to strengthen the socio-economic resilience of the Anambas community while promoting sustainable development based on local potential.